2021
DOI: 10.1186/s12889-021-12109-5
|View full text |Cite
|
Sign up to set email alerts
|

Mental distress among young adults – gender differences in the role of social support

Abstract: Background The aim of the present study was to examine to what extent observed gender differences in mental health are associated with the protective factors social support, sense of coherence and participation in regular physical activity and more generally, engagement in organized or unorganized activity with other people. Methods This study was based upon a cross-sectional regional health survey in Norway, conducted during the winter of 2015–201… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 73 publications
1
8
0
1
Order By: Relevance
“…This finding is consistent with other studies in Sudan, Canada, Indonesia, and Ethiopia [4] [8] [13] [14]. Studies in the general population found that young women aged 18 -24 years old have a higher prevalence of mental distress as compared to men in their age group [19]. The variation could be due to gender differences in experiencing and expressing mental health problems.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is consistent with other studies in Sudan, Canada, Indonesia, and Ethiopia [4] [8] [13] [14]. Studies in the general population found that young women aged 18 -24 years old have a higher prevalence of mental distress as compared to men in their age group [19]. The variation could be due to gender differences in experiencing and expressing mental health problems.…”
Section: Discussionsupporting
confidence: 91%
“…Men experience more externalized disorders such as substance abuse and dependence [20]. The gender difference in the prevalence of mental distress could also be due to physiological or social factors related to the different roles of men and women in society [19]. Genders also differ in the degree of their response to mental health interventions.…”
Section: Discussionmentioning
confidence: 99%
“…First, we had adequate power to draw statistical inference from our study findings. Second, the sample was randomly drawn from the municipalities of three large counties, representing a large proportion of the Norwegian population 30 , 31 . Third, the data on education and personal income were obtained from the national population-based registers of Statistics Norway, which largely reduces the possibility of information bias and ensures available data for the large majority of participants.…”
Section: Discussionmentioning
confidence: 99%
“…The sample was proportional to the population in each region within the three counties. The overall response rate was 42.7% (9692 respondents) 30 , 31 . Information from the population registry (municipality, age, and sex) was delivered along with the questionnaire data.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation